Evaluasi Kelas Kemampuan Lahan dan Usaha Perbaikan di Sebagian Das Riawajo Kabupaten Sikka - Bolly, Yovita Yasintha; Nirmalasari, M.A. Yohanita; Mutiara, Charly (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2021)
Agricultural activity in several villages in the Riawajo Watershed (DAS) is very high. The high agricultural activity will affect the quality of the watershed. For this reason, it is necessary to conduct research on evaluating land capability classes in the Riawajo watershed, Sikka Regency. The variables observed were soil texture, salinity, soil structure, slope, effective depth of soil, erosion damage, rock conditions, flood threat, and drainage. The data is processed by the arithmetic matching method. The results showed that the agricultural lands in the villages in the Riawajo watershed were in the first class and were still able to support their agricultural activities.